The Sustainability of Cash Waqf Using Blockchain Technology: a Conceptual Study - Anwar, Intan Fatimah; Rahayu, Syarifah Bahiyah; Yusoff, Yuslina; Lajin, Noor Faizah Mohd; Atan, Atika (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2024)
This paper explores the potential of integrating blockchain technology to enhance the sustainability of cash waqf, a significant Islamic endowment supporting charitable causes. Traditional cash waqf systems are facing challenges such as opacity, accountability gaps and inefficiency. The study provides a comprehensive overview of cash waqf and blockchain technology, exploring their synergies and potential in managing cash waqf initiatives. Through a detailed examination of challenges and opportunities, the paper establishes a robust research framework incorporating experience, knowledge, and blockchain to influence cash waqf sustainability. The proposed integration includes designing a blockchain architecture, implementing a blockchain-based cash waqf system and conducting security and privacy assessments for long-term viability. Research findings show blockchain's transformative impact, demonstrating its potential to enhance transparency, reduce fraud, increase accountability, and improve overall efficiency in managing and distributing cash waqf funds. For future work, continued exploration is needed to implement and assess the proposed blockchain integration in real-world cash waqf scenarios. The effectiveness of the system should be evaluated over an extended period, considering diverse community needs and regulatory contexts. In conclusion, conceptual research lays a foundation for a more sustainable future for cash waqf in redefining the landscape of charitable activities